1969
DOI: 10.1139/m69-222
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Graphium sp. on natural gas

Abstract: A fungus which grows well on a mineral salts solution with natural gas as the carbon source is described and provisionally identified as a Graphium species. Its taxonomic relation to several genera is presented. This organism was isolated from sewage after selection by enrichment techniques and continuous culture. The fermentor was operated at ambient temperatures, 28 °C ± 2, at a volume of 10 liters with a dilution rate of 10 liters/4 days to 10 liters/1.7 days. Coty's mineral salts medium gave the highest ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This unusual organism was first isolated from enrichment cultures grown on natural gas (11,48). In addition to growth on nonmethane n-alkanes, we have shown that this Graphium sp.…”
mentioning
confidence: 78%
“…This unusual organism was first isolated from enrichment cultures grown on natural gas (11,48). In addition to growth on nonmethane n-alkanes, we have shown that this Graphium sp.…”
mentioning
confidence: 78%
“…Its occurrence is promoted in manure-enriched or polluted environments, such as agricultural and garden soil [35 Á37], sewer [38], or ditch mud and polluted pond bottoms [39,40]. It is also found in hydrocarbon-contaminated soils [41], being able to assimilate natural gas [42,43] and aromatic compounds [44] and has therefore been suggested for use in bioremediation [45]. All these environments are poorly aerated; the fungus is able to grow at low oxygen tensions, and even shows activity under strictly anaerobic conditions [39].…”
Section: Environmental Occurrence and Transmissionmentioning
confidence: 99%
“…However, the recent experience of several groups of workers has made it clear that it is possible to isolate a large variety of bacterial types that can grow solely at the expense of meth ane (14,15,17,43,80,85,110,112). Reports of algae (24) and fungi (114) being able to grow upon methane are much less convincing, because direct demonstrations of methane utilization have not been provided.…”
Section: Methane-oxidizing Bacteria: Morphology and Physiologymentioning
confidence: 99%